Stress Management For Good Physical And Mental Health - Upadhyaya, K.D. (Journal of Psychiatrists’ Association of Nepal, 2017)
Stress can have a negative impact on just about every part of your body. It can suppress your immune system, cause a heart attack, or stroke, increase your risk of cancer, delay wound healing, promote inflammation, cause you to gain weight, impair your memory, cause depression, exacerbate diabetes and worsen your sexual function. Stress also makes you age faster….Dean Ornish MD : The Spectrum Stress is a physical or emotional reaction / response to any kind of change which may be external, internal or both. External pressure for example can be due to job stress, competition, challenges or frequently changing government policies etc. Internal pressure is mainly due to negative thoughts, fear, and anxiety. There is a individual variation in stress response. Many people have inner strength or resilience to manage day to day stress and cumulative stress well. People who have learned to manage stress also minimize the effect of stress. Those who do not have good inner strength and who have not learned the management of stress suffer a lot because of stress. Whenever there is stress, brain tells the body to release some chemicals so that the body is ready for the fight or flight reaction to deal with immediate danger.